KEPENTINGAN EKONOMI POLITIK RUSIA DALAM KERJASAMA INTERNASIONAL BRICS (BRAZIL, RUSIA, INDIA, CHINA, SOUTH AFRICA) - Palamani, Siti Mawaddah; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is talking about international partnership between countries. In this research, writer taking perspective from Russia’s interest in BRICS partnership, and the level analysis is Nation-State. BRICS is an acronym of countries, that determine themselves as an anti-Western international partnership. This research using the library research to get data and create an analysis of Russia’s importancy inside of BRICS. There is so much things in BRICS that Russia can develop, such as trading, finance, political interest, currency, and many more.There is a lot of advantages that Russia could achieve from BRICS partnership. Such as international trade among countries inside of BRICS, taking a loan from BRICS Contingent Reserve Arrangement, and strengthening Russia’s currency inside of New Development Bank. Also being in BRICS partnership would make Russia gain more political power, to get alliances of economic and political issues, and help Russia to improve their potential resources.Keywords : BRICS, Russia, International Political Economy, International Partnership